The poor prognosis of sarcomatoid carcinoma arising from low grade serous ovarian cancer: A case report and review of the literature - Paulina Haight; Johanna Savage; Kristin Bixel (Elsevier, 2021)
Sarcomatoid or anaplastic carcinomas arising within epithelial ovarian neoplasms are rare, particularly within serous tumors of the ovary, and carry a poor prognosis. Here we present the case of a patient initially diagnosed with low grade serous ovarian carcinoma arising within a serous borderline tumor (atypical proliferative serous tumor). She underwent rapid progression of disease and was found to have anaplastic/sarcomatoid carcinoma on biopsy of recurrence. These findings prompted pathologic re-review of the original neoplasm, which demonstrated a microscopic focus of sarcomatoid/anaplastic carcinoma.